Sir William Edward Maxwell: his life and contributions in british Malaya. - Moho Pakri, Mohamad Rashidi
This above research paper draws together and evaluates a number of historical events that took place during the early period of British colonization of Malaya, especially those that involved the official duties and the personal life of Sir William Edward Maxwell (especially in relation to his colleague, Sir F.A Swettenham).